Implementasi Pelatihan Tari Daerah dalam Melestarikan Tarian Banten di Sanggar Raksa Budaya Kota Serang - Nurjaman, Fatmawati; Sudadio, Sudadio; Faturohman, Nandang (Journal of Nonformal Education and Community Empowerment, 2017)
This study aims to determine the process, outcomes, supporting factors and inhibiting the implementation of local dance training in preserving the Banten dance in Serang City Culture Ritual Serang. The research approach used is qualitative approach with descriptive method. Data collection techniques used were interviews, observation, and documentation. Sources of research data are 1 instructor and 5 trainees. The validity of data using triangulation of sources, methods, and theories. Data analysis uses reduction, presentation, and conclusion. The results show the implementation process of dance training area that can be seen from the planning, implementation, and evaluation. The results of the training have increased skills and knowledge of participants and mastery of dance Banten. Factors supporting the existence of learning facilities, places of learning and a conducive community environment. The inhibiting factors are motivation, external cultural influences, and low public interest that less appreciate dance area of Banten.